G435(P) Making every contact count – a paediatric pilot training programme in wales. (12th March 2018) - Webster, S
Abstract : Introduction: A key recommended from the RCPCH State of Child Health report includes health promotion training for health professionals in order to 'make every contact count' (MECC). In order to pilot such a resource, a Public health training programme providing an evidence-based approach to motivational interviewing for behaviour change was adapted for those within the paediatric profession. Methods: The 'Making every contact count' level 1 and 2 training programme was adapted and combined into a two-hour training session. This was delivered at a paediatric trainee study day in May 2017 and a health board clinical governance day in July 2017. Results: There were 41 trainees in attendance at the trainee study day. 14 paediatric consultants and 24 paediatric nurses attended the clinical governance session. A total of 57/79 (73%) matched pre- and post-evaluation questionnaires were included for feedback analysis. Through a 5 point Likert scale the pre-session survey highlighted 57% (32/57) strongly agreed of the importance of MECC; this rose to 75% (43/57) post-session. 84% (47/57) were confident with MECC skills pre-session, however this fell to 77% (44/57) post-session. Individuals reported questioning their ability to discuss healthy lifestyle behaviours and recognised the benefit of a structured approach to motivational interviewing. Those confident in their knowledge base of healthy lifestyles advice rose from 11% (6/57) to 29% (16/57). Confidence in the approach to conversation rose from 38% (21/57) to 56% (31/57); and in having a response to disengagement from patients and carers rose from 22% (12/57) to 52% (29/57). Knowledge of local resources, and where to signpost individuals to, also saw a rise from 16% (9/57) to 46% (26/57), and 8% (4) to 39% (22/57) respectively. Conclusion: Despite the evidence base for this Public health educational programme originating from adult research, adapted to aid professionals caring for children and young people has proved its worth as a useful resource. A collaborative approach with local public health teams would allow for this programme to be developed bespoke to local areas and would be a useful tool for motivational interviewing with children, young people and their carers to improve health lifestyles.